2004
DOI: 10.1007/s10228-003-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations estimated from PCR-RFLP analysis of two morphs of the freshwater goby Rhinogobius in the Lake Biwa water system

Abstract: The freshwater goby Rhinogobius is the most abundant fish in the shore area of Lake Biwa, Japan. Recently, it has been reported that two morphs of Rhinogobius inhabit this lake. In this study, genetic variations in Rhinogobius sp. OR (Orange-type) and Rhinogobius sp. BW (Biwa-type) in the Lake Biwa water system have been investigated using polymerase chain reaction-based restriction fragment length polymorphism (PCR-RFLP) analysis of mitochondrial DNA, including the variable D-loop region. Samples of Rhinogobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…OR and Rhinogobius sp. BW, there are no genetic differences among populations in Lake Biwa, probably due to wide dispersal of their planktonic larvae (Takahashi & Ohara 2004). If, like these Rhinogobius species, T. brevispinis is also widely distributed along shorelines at the end of the planktonic larval period, there are unlikely to be genetic differences among populations, and the difference in age at maturity of males between the Ohmi-maiko and Minamihama populations probably results from plasticity of life-history traits.…”
Section: Discussionmentioning
confidence: 96%
“…OR and Rhinogobius sp. BW, there are no genetic differences among populations in Lake Biwa, probably due to wide dispersal of their planktonic larvae (Takahashi & Ohara 2004). If, like these Rhinogobius species, T. brevispinis is also widely distributed along shorelines at the end of the planktonic larval period, there are unlikely to be genetic differences among populations, and the difference in age at maturity of males between the Ohmi-maiko and Minamihama populations probably results from plasticity of life-history traits.…”
Section: Discussionmentioning
confidence: 96%
“…In case of a genetic effect, the differential behavioural response would have evolved separately in the two populations to fit respective environments. Previous molecular analyses, however, have shown that the gene pool is shared by the two population types (Takahashi & Okazaki, 2002; Takahashi & Ohara, 2004). The extent to which this species is divergent is so limited to be virtually undetectable by molecular analyses, even if a genetic effect exists.…”
Section: Discussionmentioning
confidence: 99%
“…They have distinct spawning locations between which they can, but seldom, migrate, as shown by isotopic analysis (Maruyama et al , 2001). They both spend the larval period in the lake and molecular data suggest they share a common gene pool (Takahashi & Okazaki, 2002; Takahashi & Ohara, 2004). The fluvial population migrates upstream from the lake to the tributary rivers at the age 0+ years (Yuma et al , 2000) and spawns larger eggs in rapids or glides (Maruyama et al , 2003, 2004), where the flow maintains dissolved oxygen concentration near saturation (Allan, 1995; Hauer & Hill, 1996).…”
Section: Introductionmentioning
confidence: 99%